Tax and the UK post-Brexit: introduction to the Brexit articles - Loutzenhiser, G (Sweet & Maxwell, 2022)
Introduces a special issue of B.T.R. on the complexities Brexit poses for UK taxation, including the politico-economic context, the extent to which Brexit is responsible for economic disruption, the tax opportunities Brexit offers, state aid developments, and the impact of ECJ cases on UK tax law.